Die Bedeutung der Emotionalen Intelligenz für die Projektmanagement-Praxis - Constantin Schubart; Christin Nagel (IU Internationale Hochschule, 2022)
– Based on the current state of research on emotional intelligence in project management, an empirical study is used to examine and evaluate the influence of emotional intelligence on project management in practice. Finally, recommendations for action for project management practice are derived. In project management practice, the competence of emotional intelligence is characterized by empathy, the ability to work in a team, and the ability to deal with conflict as competence elements. Particularly in agile and hybrid projects and in the implementation phase of projects, this competence is of great importance and should therefore be taken into account as an equal competence alongside technical and methodological competence when putting together the project team. The relevance of emotional intelligence is independent of the complexity of the project and the degree of innovation of the project. The project team size and project duration also have no reinforcing or diminishing influence on the relevance of emotional intelligence for project management.
Keywords: M14; 650; Projektmanagement; Kompetenzen; Emotionale Intelligenz